Gravitation, cosmology and dark matter - Valenzuela, Mississippi (2023)
In this work, we present the fundamentals of the general theory of relativity, the standard cosmology and a description of current and interesting research topics about our current Universe, in addition the emergence of the dark matter problem has been raised, trying to outline possible dark matter candidates. This assumption seems realistic, however the analysis, from the point of view of standard cosmology, which is also studied in this work, turns out to be more complex than if dark matter were considered with a single species of elementary particle.